Appropriate measures to use money laundering prevention as an antidote to tax evasion - Patricia Torres Serpel; Amir Shachmurove (The Journal of Entrepreneurial Finance and Business Ventures, 2005)
Money laundering, which is closely linked with tax evasion and informal trade, is facilitated by the poorly regulated financial institutions of mafia nations. These nations make billions of dollars by laundering money and giving safe haven to drug dealers and corrupt politicians, allowing them to transfer money globally. Money laundering prevention policies require financial institutions to periodically update their customer's personal information. Furthermore, they attempt to match tax and transaction reports collected from banks and non-banks around the world to detect tax evasion. This research explains how efficient policies for preventing money laundering can help reduce tax evasion.
Keywords: 650